Origin, localization and binding abilities of boar DQH sperm surface protein tested by specific monoclonal antibodies - Postlerová, Pavla; Pěknicová, Jana; Elzeinová, Fatima; Tichá, Marie; Jonáková, Věra (Journal of reproductive immunology, 2007)
Seminal plasma proteins bind the sperm surface at ejaculation and may modulate several aspects of sperm activity during reproduction. DQH sperm surface protein, present in boar seminal plasma, shows affinity to phoshorylcholine, acidic polysaccharides, oviductal epithelium and zona pellucida glycoproteins. Monoclonal antibodies (MAbs) against DQH protein were prepared and used for determination of the DQH protein origin in boar reproductive organs, its localization on boar spermatozoa, and for investigation of its binding abilities in the porcine oviduct and to the zona pellucida of the oocyte. The mRNA transcript of DQH protein was found in seminal vesicles and not in the testis, epididymis and prostate. Its translated products were immunodetected by MAbs in seminal vesicle extract and fluid, in seminal vesicle tissue sections and on the membrane-associated acrosomal part of ejaculated spermatozoa. These results confirm the ability of DQH protein to bind the sperm surface at ejaculation and to participate in formation of the sperm reservoir in the porcine oviduct. Moreover, monoclonal antibodies reduced binding of sperm to oocytes and proved the role of DQH protein in the sperm-zona pellucida primary binding.
Keywords: sperma; spermie; Humans; Fallopian Tubes; Sperm-Ovum Interactions; Protein Binding; Antibodies, Monoclonal; fertilizace; Female; Zona Pellucida; polymerázová řetězová reakce s reverzní transkripcí; financování organizované; mužské pohlavní orgány; Financing, Organized; lidé; Reverse Transcriptase Polymerase Chain Reaction; zvířata; Immunohistochemistry; imunohistochemie; Membrane Glycoproteins; membránové glykoproteiny; Genitalia, Male; interakce spermie a vajíčka; Swine; Fertilization; Seminal Plasma Proteins; ženské pohlaví; Male; vazba proteinů; monoklonální protilátky; Semen; zona pellucida; proteiny semenné plazmy; vejcovody; Spermatozoa; Animals; mužské pohlaví; prasata